Transition Words Progression of Written Texts Made by the Second-Semester Students of the English Study Program of FKIP Saint Thomas University in Academic Year 2019/2020 - Fiber Yun Almanda Ginting (Britain International for Academic Research (BIAR) Publisher, 2021)
This research is written to achieve an objective as follow: (1) to find out the progression of transitional in writing text has been made by the second semester of English Education Study Program in academic 2018/2019. The writer used descriptive qualitative research to give description systematically and factually about facts of a certain population. The researcher determines that the design is descriptive quantitative method because it describes the data that is taken from the sample, and the results of the data were tabulated in the form of percentage. There were 18 students (90%) agreed that transition words were used to connect the sentences. There were 20 (100%) students (90%) agreed that transition words were used to organize the sentences. There were 17 students (85%) agreed that transition words were used to remember about the topic. There were 20 (100%) students agreed that transition words were used to tell the experience, and there were 20 (100%) students agreed transition words were used to enhance the connections between facts.